Implementation of Evaluation of Learning in The Psychomotor Domain of Islamic Religious Education and Ethics at Smpit Ar-Risalah Sukoharjo - Azzahra, Faritsa; Maksum, Muh. Nur Rochim (Journal of Educational Sciences, 2025)
Evaluation of learning in the psychomotor domain is also important in the learning process in addition to the cognitive and affective domain. This study aims to find out how to implement the evaluation of learning in the psychomotor domain of Islamic Religious Education and Ethics at SMPIT Ar-Risalah Sukoharjo and to find out the obstacles experienced in the process of implementing the evaluation of learning in the psychomotor domain in the subject of Islamic Religious Education and Ethics at SMPIT Ar-Risalah Sukoharjo. This type of research uses qualitative research by directly going into the field. The data collection method used was through interviews, observations and documentation. This study uses the Miles and Huberman model data analysis technique which consists of data reduction, data presentation and conclusion drawn. Based on the conclusion of the results of this study, the implementation of the evaluation of Psychomotor Learning in the Field of Islamic Religious Education and Ethics at SMPIT Ar-Risalah Sukoharjo has carried out an evaluation by adjusting the existing material and the needs of students in daily life such as worship practices. However, in its implementation, maple teachers have obstacles such as time limitations and the preparation of appropriate assessment rubics.